Novel adaptive branching constraint solving algorithm with look-ahead strategy - Hai-yan WANG; YANGDan-tong OU; Yong-gang ZHANG; Liang ZHANG (Tongxin xuebao)
Based on the state-of-the-art scheme of adaptive branching constraint solving, a novel algorithm named AdaptBranchLVOwas proposed, combined with the look-ahead value ordering heuristics. To demonstrate the efficiency of AdaptBranchLVO, sufficient experiments on the wide range of the problem instances in Benchmark were carried out, and the experiment results show that AdaptBranchLVOoutperforms the existing adaptive branching constraint algorithm by a large margin.